PERSONNEL DEVELOPMENT MODEL OF SAVINGS COOPERATIVE - Khoboon, Thanee (Journal of MCU Nakhondhat, 2023)
This academic article aims to present a model for personnel development of savings cooperatives. which was synthesized from documents Articles and research related to human capital development in organizations Improving the quality of work, knowledge and personnel development models from academics in the country and abroad. along with a synthesis of 4 models of human resource development of Sakon Nakhon Provincial Savings Cooperatives, consisting of Model 1 Development of basic knowledge and operating processes Develop the core aspects of operations, including 1) Orientation for new personnel 2) Training while stationed 3) Continuing education 4) Dissemination of academic news. Model 2: Developing and increasing efficiency It is development after coming to work, consisting of 1) Training while stationed, 2) Seminars by experts, 3) Job teaching, 4) Workshops, 5) Transfer of duties, 6) Work assignments, 7) Finding a senior to help. Teach the job. 8) Providing security guards instead. 9) Act as a work assistant 10) Observe work 11) Do an internship to enhance skills in some way. 12) Organizing short training sessions 13) Training to introduce work 14) Organizing general academic training to increase knowledge according to the needs of officials 15) Sending officials to attend short-term academic training organized by other agencies on a regular basis. Time. Model 3: Leadership development consists of 1) Training while stationed, 2) Study tours in the organization, 3) Trainer training, 4) Participation assignments. in solving problems that arise between departments 5) Education and training of lecturers and Model 4, other developments Related topics include 1) Communication and teamwork, 2) Human relations between personnel and the community, 3) Creativity and innovation.